Characterization of a Major Bacillus anthracis Spore Coat Protein and Its Role in Spore Inactivation - Kim, Ho-San (American Society for Microbiology, 2004)
A major Bacillus anthracis spore coat protein of 13.4 kDa, designated Cotα, was found only in the Bacillus cereus group. A stable ca. 30-kDa dimer of this protein was also present in spore coat extracts. Cotα, which is encoded by a monocistronic gene, was first detected late in sporulation, consistent with a σ(K)-regulated gene. On the basis of immunogold labeling, the protein is in the outer spore coat and absent from the exosporium. In addition, disruption of the gene encoding Cotα resulted in spores lacking a dark-staining outer spore coat in thin-section electron micrographs. The mutant spores were stable upon heating or storage, germinated at the same rate as the wild type, and were resistant to lysozyme. They were, however, more sensitive than the wild type to phenol, chloroform, and hypochlorite but more resistant to diethylpyrocarbonate. In all cases, resistance or sensitivity to these reagents was restored by introducing a clone of the cotα gene into the mutant. Since Cotα is an abundant outer spore coat protein of the B. cereus group with a prominent role in spore resistance and sensitivity, it is a promising target for the inactivation of B. anthracis spores.